Teknologi Ekstraksi Bunga Kenanga (Cananga Odorata L.) dan Sereh Wangi (Cymbopogon Nardus L. ) Sebagai Aroma Terapi Sabun Cair - Malse Anggia; Sri Mutiar; Dewi Arziah (Universitas Batanghari Jambi, 2018)
Essential oils are used as raw materials in various industries. Plants containing essential oils are flower kenanga and citronella fragrance. This study aims to create prototype of essential oil distillation equipment. Essential oils obtained from the prototype, then tested as an aroma therapy in liquid soap. The result of oil refining has been done several experiments by using citronella fragrance and kenanga flower. Device productivity goes well. This is indicated by the oil obtained from lemongrass and kenanga oil in the process of distillation. The resulting volatile oil is applied to the manufacture of liquid soap. Yield oil yields were 0.22%. and the fragrant lemongrass obtained is 0.12%. Based on the organoletic test on the resulting soap product, the average of the color is 3.7 (likes), the viscosity is 3.55 (likes), the aroma is 3.05 (regular) and the 3.55 foam (likes) on the kenanga aroma soy while the average color is 4.05 (like) viscosity 3.1 (regular), aroma 3.05 (regular) and foam 3.45 (likes) on liquid soap the aroma of citronella perfume. Keywords : Essential oil; Extraction; Lemongrass; Soap